Comprehensive diagnosis and treatment of alveolar echinococcosis: A single-center, long-term observational study of 312 patients in Germany - Grüner, Beate; Kern, Petra; Mayer, Benjamin; Gräter, Tilmann; Hillenbrand, Andreas; Barth, Thomas E. F.; Muche, Rainer; Henne-Bruns, Doris; Kratzer, Wolfgang; Kern, Peter (GMS Infectious Diseases, 2017)
Alveolar echinococcosis (AE) is the most Iethal human helminthic infection. The malignancy-like disease is rare, but morbidity and treatment costs are high. Objective of the study was to identify factors at baseline and during specific AE therapy influencing the long-term outcome of the disease.All patients with AE seen at the specialized treatment unit in Ulm between January 1992 and December 2011 were included in the analysis.The data of 312 patients were analyzed; 108 were diagnosed before 2000 (series A), 204 since 2000 (series B); 290 received specific AE treatment. Patients of series B were more often symptom-free at diagnosis (44.1% vs. 21.3%), had lower disease stages (50.0% vs. 34.2%) and more complete resections (57.7% vs. 20.0%), but higher rates of side effects and drug toxicity (54.1% vs. 40.8%). In series B, more patients remained relapse- or progression-free after 5 years (90.5% vs. 82.8%); after 10 years, the ratio of relapses converged (70.3% vs. 66.9%, p=0.0507). Relapses or progression occurred more often after incomplete surgery or long treatment pauses. The 5-year and 10-year survival rates were 96.9% and 90.6%, respectively, and 17% of the patients were cured.We observed a shift towards early diagnosis, earlier initiation of specific therapy and more complete resections after 2000. Although diagnosis and treatment of AE pose a challenge, with an individual interdisciplinary management 88.8% of the patients have a favorable outcome.